11Boron Delivery Agents for Boron Proton-capture Enhanced Proton Therapy - Hideghéty, Katalin; Brunner, Szilvia; Cheesman, Andrew; Szabó, Emilia Rita; Polanek, Róbert; Margarone, Daniele; Tőkés, Tünde; Mogyorósi, Károly (Anticancer research, 2019)
The aim of this review was to define appropriate 11B delivery agents for boron proton-capture enhanced proton therapy (BPCEPT) taking into account the accumulated knowledge on boron compounds used for boron neutron capture therapy (BNCT). BPCEPT is a promising treatment approach which uses a high linear energy transfer (LET) dose component in conjunction with conventional proton therapy to increase the relative biological effectiveness of highly-selective charged particle therapy. Boron proton fusion reactions occur with highest cross section at certain proton energy level and thus can be tailored to the target volume with careful treatment planning that defines the 675 MeV proton distribution with high accuracy. Appropriate 11B compounds are required in order to achieve relevant high LET dose contribution from the boron proton-capture reaction. Previous scientific results and experiences with BNCT provide background knowledge and information regarding the optimization of boronated compound development, their characterization, measurement and imaging. However, there are substantial differences between BNCT and BPCEPT, which in turn places special unique chemical, physical and biological demands on 11B-carrier compounds for BPCEPT. In this review, we evaluate well-known and recently developed boron compounds for BPCEPT.
Keywords: Boron; Linear Energy Transfer; Brain Neoplasms; Protons; review; Boron delivery agents; Humans; BNCT; terapie metodou neutronového záchytu (bor-10); nádory mozku; lineární přenos energie; lidé; bor; boron-neutron capture therapy; boron-proton capture enhanced proton therapy BPCEPT; protony; Boron Neutron Capture Therapy